Case Report: Hypothalamic Amenorrhea Following COVID-19 Infection and Review of Literatures - Facondo, Paolo; Maltese, Virginia; Delbarba, Andrea; Pirola, Ilenia; Rotondi, Mario; Ferlin, Alberto; Cappelli, Carlo (Frontiers in Endocrinology, 2022)
SARS-CoV-2 infection, responsible for the coronavirus disease 2019 (COVID-19), can impair any organ system including endocrine glands. However, hypothalamic–pituitary dysfunctions following SARS-CoV-2 infection remain largely unexplored. We described a case of hypothalamic amenorrhea following SARS-CoV-2 infection in a 36-year-old healthy woman. The diagnostic workup excluded all the causes of secondary amenorrhea, in agreement to the current guidelines, whereas the gonadotropin increase in response to GnRH analogue tests was suggestive for hypothalamic impairment. Therefore, since our patient did not present any organic cause of hypothalamic–pituitary disorder, we hypothesized that her hypothalamic deficiency may have been a consequence of SARS-CoV-2 infection. This assumption, besides on the temporal consecutio, is strengthened by the fact that SARS-CoV-2 infection can impair the hypothalamic circuits, altering the endocrine axes, given that angiotensin-converting enzyme 2 receptors have also been observed in the hypothalamus. We reviewed the literature regarding hypothalamic–pituitary dysfunction in patients with SARS-CoV-2 infection. No study has previously described female hypogonadotropic hypogonadism with secondary amenorrhea following COVID-19. We suggest clinicians focusing greater attention on this possible endocrine disorder.